How to change everything : the young human's guide to protecting the planet and each other - Klein, Naomi, 1970- (Penguin Books, 2021)
"An empowering, engaging young readers guide to understanding and battling climate change from the expert and bestselling author of This Changes Everything and On Fire, Naomi Klein. Warmer temperatures. Fires in the Amazon. Superstorms. These are just some of the effects of climate change that we are already experiencing. The good news is that we can all do something about it. A movement is already underway to combat not only the environmental effects of climate change but also to fight for climate justice and make a fair and livable future possible for everyone. And young people are not just part of that movement, they are leading the way. They are showing us that this moment of danger is also a moment of great opportunity-an opportunity to change everything. Full of empowering stories of young leaders all over the world, this information-packed book from award-winning journalist and one of the foremost voices for climate justice, Naomi Klein, offers young readers a comprehensive look at the state of the climate today and how we got here, while also providing the tools they need to join this fight to protect and reshape the planet they will inherit"--